Using an ontology and metamodels to evaluate systems engineering (SE) domain-specific modeling languages (DSML) - Rudder, Sarah, author; Herber, Daniel R., advisor; Adams, Jim, committee member; Burt, Melissa, committee member; Coburn, Tim, committee member; Daily, Jeremy, committee member; Fields, David, committee member (Colorado State University. Libraries, 2026)
Advances in the technologies available to systems engineering (SE) have led to an increase in domain-specific modeling languages (DSML). These define concepts and the relationships between them with a metamodel that addresses the syntax and semantics of the DSML. While meant to enable specialized capabilities, this diversity introduces challenges regarding model interoperability and data translation. This research explores the relevance of a subset of prominent languages --- the Unified Modeling Language (UML) v2.5.1, Systems Modeling Language (SysML) v1.7, CubeSat Reference Model (CSRM) v1.0, Unified Architecture Framework Modeling Language (UAFML) v1.2, Comprehensive System Design Language (CSDL) v1, Lifecycle Modeling Language (LML) v2.0, and SysML v2.0 --- to the SE discipline. To evaluate the pertinent concepts of each DSML, it is necessary to have a deep understanding of SE, its processes, and its goals. To capture this foundational knowledge, a domain-specific ontology (DSO) is constructed by leveraging the normative reference ISO 15288:2023, the Web Ontology Language (OWL), and the open-source editor, Protégé. Both the DSML metamodels and the SE DSO are represented as concept models within an SE tool. This method facilitates the mapping of Equivalent Classes between DSML terms and ISO 15288. These mappings assist in the alignment of languages with core SE concepts and concludes with recommendations for DSML developers and practitioners. Finally, this work supports the organizational goals of Enola Technologies, LLC, by providing concrete evidence that assists with knowledgeably answering customer questions and alleviating their concerns
Keywords: metamodels; systems engineering; ontology; domain-specific modeling languages